Diseño y aplicación de un programa cognitivo conductual para el desarrollo y adquisición de conductas prosociales en niños con agresividad de 9 a 12 años de la escuela Atanasio Viteri - Cáceres Bonilla, Mónica Ivonne (2015)
A psychological intervention was performed on a group of children with ages between 9 and 12 years old. These children were students at the Atanasio Viteri school, located in Carcelén Bajo, Quito Ecuador. They manifested aggressive behaviors and a lack of some variables incompatible with aggressiveness, such as basic social skills and interpersonal troubleshooting skills. Therefore, a cognitive-behavioral program was designed which objective was the acquirement and development of pro social behaviors and decrease the aggressiveness before the intervention a pretreatment evaluation was made through the use of psychometric tests from the social interaction skill questionnaire CHIS (Monjas, 1994) and The Matson Evaluation of Social Skills with Youngsters MESSY (Matson, Rotatori & Helsel, 1983), with the purpose of identifying the clinic sample. Once the intervention was done, the same instruments were applied in order to contrast the obtained results which are shown, statistically analyzed and discuss.